Determinación del ciclo de vida de las películas de tio2/cuo/Ag y su efecto antimicrobiano sobre E.coli en luz visible (2018)
In this research project the preparation of a mixture of titanium dioxide (TiO2) with copper oxide (CuO) and silver (Ag) was carried out. The preparation of the TiO2 / CuO mixture was made by the wet impregnation method, the suspension of this mixture was made by means of the Ultra-turrax, which was deposited in glass by the Spin Coating method to form the required films, which then they were modified again with Silver Nitrate (AgNO3) to reach this modification. For the functionality test of the films, Methylene Blue was used as an indicator of the degradation in the visible spectrum. The efficiency of the mixture for the inactivation of E.coli was evaluated by means of a reactor, where the reaction was carried out in a time of 9 hours, taking samples at hour 0, 4 and 9, after this the dilutions were made and it was proceeded to add this dilution in the Petrifilm coliform count plates, then the microorganism was counted by the plate count technique. The best degradation was obtained with the modified film of TiO2 / CuO / Ag deposited at 1000rpm, since it reduced around 2 ppm in only 60 minutes, showing the best adhesion, and homogeneity of the deposited suspensión.